Pelayanan Keagamaan di Wilayah Perbatasan - Sabara Nuruddin (Pusat Pengembangan dan Pelatihan dan Kajian Manajemen Pemerintahan Lembaga Administrasi Negara, 2019)
This study focuses on the description of religious services in border communities in Sebatik Tengah District. what about religious services carried out by the ministry of religion in the Sebatik Tengah District and the problems in providing these religious services? Religious services referred to in this study are religious services facilitated by the ministry of religion as the service provider which includes; KUA service tasks and functions, religious counseling services, religious education services and religious harmony services. Religious services provided are still very limited due to the lack of facilities and service resources. KUA services are still in the KUA North Sebatik District working area and are still focused on marriage registration services and prospective bride courses. Religious education services are carried out by the private sector facilitated by the ministry of religion in the form of Raudhatul Atfaldan Madrasah Ibtidaiyah and Diniyah. Religious healing services are served by four non-PNS Islamic religious instructors who are still very limited in their range of services. Religious harmony services through FKUB Subdistrict where the head of the KUA also doubles jon as the leader and involves figures from three religions (Islam, Catholicism and Christianity) in the District of Sebatik Tengah. The main problems in the provision of religious services are service infrastructure, service provider human resources and lack of budget